Developmental co‐occurrence of psychopathology dimensions in childhood - Andrea G. Allegrini; Toos vanBeijsterveldt; Dorret I. Boomsma; Kaili Rimfeld; Jean‐Baptiste Pingault; Robert Plomin; Meike Bartels; Michel G. Nivard (Wiley, 2022)
Abstract Background Comorbidity between psychopathologies may be attributed to genetic and environmental differences between people as well as causal processes within individuals, where one pathology increases risk for another. Disentangling between‐person (co)variance from within‐person processes of psychopathology dimensions across childhood may shed light on developmental causes of comorbid mental health problems. Here, we aim to determine whether and to what extent directional relationships between psychopathology dimensions within‐person, and between individuals within families, play a role in comorbidity. Methods We conducted random intercepts cross‐lagged panel model (RI‐CLPM) analyses to unravel the longitudinal co‐occurrence of child psychopathology dimensions, jointly estimating between‐person and within‐person processes from childhood to early adolescence (age 7-12). We further developed an extension of the model to estimate sibling effects within‐family (wf‐RI‐CLPM). Analyses were separately conducted in two large population‐based cohorts, TEDS and NTR, including parent‐rated measures of child problem behaviours based on the SDQ and CBCL scales respectively. Results We found evidence for strong between‐person effects underlying the positive intercorrelation between problem behaviours across time. Beyond these time‐varying within‐person processes accounted for an increasing amount of trait variance, within‐ and cross‐trait, overtime in both cohorts. Lastly, by accommodating family level data, we found evidence for reciprocal directional influences within sib‐pairs longitudinally. Conclusions Our results indicate that within‐person processes partly explain the co‐occurrence of psychopathology dimensions across childhood, and within sib‐pairs. Analyses provided substantive results on developmental processes underlying comorbidity in behavioural problems. Future studies should consider different developmental timeframes to shed more light on the processes contributing to developmental comorbidity.